Current methodologies for evaluating remineralization and biomineralization in dentistry - Citelli Conti, Leticia [UNESP]; Marques, Vanessa Abreu Sanches [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; De Castilho Jacinto, Rogério [UNESP]; De Oliveira Gallinari, Marjorie [UNESP]; Souza, Marina Trevelin; Benetti, Francine [UNESP] (My University, 2019)
The dental scientific production aims to solve the needs and problems found in the clinical routine. With the research and its results it is possible to produce knowledge that directs the professional to the improvement and change of the quality of life of the individual. Among the various challenges is the difficulty in forming and regenerating lost mineralized tissues that is present in the various areas of dentistry. Therefore, it is necessary to carry out an extensive investigation regarding these tissues, since when they lose structures, they usually present physiological or functional deficiency. It is known that biomineralization is a complex, dynamic and permanent process that involves the precipitation of inorganic substances in organic matrices to give rise to biological tissues, such as enamel, dentin, cement and bone. The remineralization occurs when there is an increase in the mineral volume of the dental tissues, through the deposit, mainly, of crystals of calcium and phosphate, after a process of demineralization. In the attempt to find solutions to these mineralizing deficiencies, the development and execution of different methodologies are essential in the search to unravel the metabolic process of the tissues and, from this information, to create bioactive materials and clinical procedures that are capable of contributing to neoformation or mineralization of the tissue. In this chapter we discussed different laboratory methodologies developed in vivo, in vitro and/or in situ with the purpose of directing the development of the research on the mineralization process.
Keywords: Biomineralization; Dentistry; Methodology; Tooth remineralization